FUZZY BASED IMAGE ENHANCEMENT THROUGH LIFTING WAVELET TRANSFORM - Laxmi Narayan Gouda; Dr. Prakash Kumar Pathak (International Journal For Research In Advanced Computer Science And Engineering, 2024)
Wavelet based logic is a form of many valued logic, it deals with reasoning that is approximate rather than fixed and exact. Compared to traditional binary sets (where variables may take on true or false values) fuzzy logic variables may have a truth value that ranges in degree between 0 and 1. Fuzzy logic has been extended to handle the concept of partial truth, where the truth value may range between completely true and completely false. When linguistic variables are used, these degrees may be managed by specific functions. Fuzzy logic has been applied to many fields, from control theory to artificial intelligence. In this paper, the traditional image enhancement algorithms enhance noise signal in image while they enhance image, which leads to the descent of information entropy. Designing image enhancement systems with good nature is a goal which all researchers pursue. Method of lifting can best deal with MRA Multi-resolution Analysis method which is time and memory consuming which impedes its real-time application. The process of lifting method was introduced. Method of image enhancement based on lifting wavelet was introduced. The algorithm and traditional wavelet image enhancement algorithms are compared. Result of the experiment indicate, the quality of image have been improved. It is better than traditional wavelet image enhancement algorithms.